Gestión del proceso de adquisición de textos académicos por medio de sofware con el fin de mejorar la calidad del acervo bibliográfico en la Universidad Técnica Estatal de Quevedo - Herrera Rentería, Wilmer Mauricio (2013)
The research demonstrates an effective solution for the thread library material selection of the Library of the State Technical University Quevedo, using technology through a software architecture based on a site called "Book Select Tool", which was built in the course of this investigation. Allows the coordinator of each race, make a selection of academic texts efficiently relative to learning units of the curriculum, taking into account the syllabus that really need books with the help of the tools of decision making software . It also allows the librarian to take decisions quickly debug, based on the number of students and books required, and thus contribute to the improvement of the necessary bibliography for each competency model syllabus. In addition to providing information necessary for the process of evaluation and institutional accreditation of fast, accurate, and reliable indicator established by CEAACES, which describes the amount of books for students with syllabi. Using the analytical method and with the aid of descriptive statistics demonstrated the advantages of this research, increasing the efficiency in the selection of library materials based on parameters such as force, requisition level and quality, and efficiency in the use of resources economic University. Upon completion of this investigation it was found that the use of computer software was very useful, providing a method for selecting library materials superior over the traditional form, based on parameters such as efficiency and effectiveness, maintaining consistency with the syllabus, and significantly improves the amount of existing texts of each learning unit.